Gender and Protests in Costa Rica (2008-2020) - Cortés Sequeira, Sofía (2022)
What have been the dynamics of progressive and conservative gender protests in Costa Rica? The objective of this research is to analyze the main trends in collective actions around the sexual, reproductive and civil rights agenda of women and sexually diverse people in Costa Rica during the period 2008-2020, paying special attention to the dynamics between actors who seek to advance this agenda, and those who seek to push it back. Through the use of the Protest Event Analysis (PEA) methodology, an outline of the gender protests, actors, repertoires of action, demands and demand instances in the period 2008-2020 is presented.